Yield, Antioxidant Activity, and Toxicity of Ethanol Extracts from Air- and Sun-Dried Sikkam Leaves (Bischofia javanica Blume) Obtained by Maceration and Soxhlet Extraction - I Wayan Muderawan; Nia Astria Br. Saragih; I Wayan Mudianta (Universitas Negeri Yogyakarta, 2026)
Sikkam (Bischofia javanica Blume) is a species of the genus Bischofia in the Euphorbiaceae family that can be used as a traditional medicine. This study aimed to determine the yield, antioxidant activity, and toxicity of sikkam leaf extract. Sikkam leaves were dried at room temperature (air-dried) and under direct sunlight (sun-dried). The extracts were obtained using the maceration and Soxhlet extraction methods with 96% ethanol as the solvent. The yields of air-dried (A-D) and sun-dried (S-D) sikkam leaf extracts isolated by maceration and Soxhlet extraction differed significantly (p<0.05), with average values of 20.48±2.30, 22.32±1.19, 24.31±2.01 and 24.71±0.09% for A-D maceration, S-D maceration, A-D Soxhlet extraction, and S-D Soxhlet extraction, respectively. The antioxidant activity (IC50) of sikkam leaf extracts, tested using the DPPH method, showed significantly different mean values (p<0.05), with the following averages: 11.13±1.30, 12.86±2.88, 11.36±1.47, and 14.82±1.19 µg/mL for A-D maceration, S-D maceration, A-D Soxhlet extraction and S-D Soxhlet extraction, respectively. The ethanol extracts of air-dried and sun-dried sikkam leaves isolated via maceration and Soxhlet extraction fall into the category of very strong antioxidant activity. The toxicity (LC50) of the sikkam leaf extracts tested using the Brine Shrimp Lethality Test (BSLT) differed significantly (p<0.05), namely 941±37, 914±67, 985±72 and 700±39 µg/mL for A-D maceration, S-D maceration, A-D Soxhlet extraction and S-D Soxhlet extraction, respectively. Ethanol extracts of air-dried and sun-dried sikkam leaves, isolated by maceration and Soxhlet extraction, are classified as non-toxic.